STUDI KOMPARATIF ABORSI DI INDONESIA DAN KOREA SELATAN DALAM PERSPEKTIF FEMINIST LEGAL THEORY - Utamie, R. Aj. Nindya Rizky (Jurnal Jendela Hukum, 2023)
Abortion in Indonesia is still considered taboo and criminalized, while abortion in South Korea is the opposite. Countries that use the same legal system do not mean their regulations are also the same. Abortion raises different opinions from Pro-Life and Pro-Choice people. Analysis of feminist legal theory, especially radical feminism, is used to see the response of Indonesia and South Korea to abortion. This research aims to: 1) determine abortion regulations in Indonesia and South Korea; and 2) analysis of feminist legal theory regarding abortion in Indonesia and South Korea. This research is normative legal research or doctrinal research, using a statutory-regulatory approach, contextual approach, and comparative study. The data sources used are primary legal materials, namely Law Number 17 of 2023 concerning Health, the Criminal Code, and Law Number 1 of 2023 concerning the Criminal Code. Secondary legal materials are in the form of literature reviews related to legal materials that are appropriate to the research topic. The research shows that abortion in Indonesia is not fully legalized, in contrast to South Korea which has lifted the ban on abortion after the decision of the South Korean Constitutional Court. Based on the analysis of Feminist Legal Theory, Indonesia still has not accepted and accommodated all forms of demands from feminism, while South Korea considers abortion to be a woman's right and what is within a woman is her full right.